Nutrition and Chronic Conditions - Ojo, Omorogieva (Nutrients, 2019)
This editorial discusses and analyses the role of dietary interventions in the management of chronic conditions in recognition of the global increase of these diseases, the rise in the ageing population, and the significant cost to health services around the world. Evidence has shown that low-glycaemic index (GI) and low-carbohydrate diets are effective in the management of type 2 diabetes, and the role of unsaturated fatty acids, vitamins, and bioactive compounds in chronic disease management have been the subject of intense research. However, although multidimensional approaches are important in the management of these chronic conditions, nutritional interventions are critical and central to these strategies.